Electronic Elections: International Experience - Napetvaridze, Vladimeri (Politics / პოლიტიკა, 2017)
The development of modern technologies has changed all spheres of human live. Communication has become faster and efficient. Process of internalization has accelerated progress and made the world more mobile. Communication forms between society and government have been changed. Society is granted with an opportunity to obtain any kind of information via internet. Furthermore, new kind of electronic services became available. Due to involvement of internet communications in the process of governance the level of society's engagement has increased. Through internet citizens can express their opinion or become authors of initiatives. Successful application of modern technologies in everyday life made it possible to conduct electronic elections. There are two ways to provide electronic elections: Traditional voting ballots are substituted by electronic machines; in this case no internet is needed;    Internet elections, when voters are voting using internet and their own computers;             The present paper will discuss successful and failed examples of electronic voting process in different countries. It will also examine readiness of Georgia to conduct electronic and internet elections.